Ludic writing: Challenges in gamifying English creative writing class for technopreneurial purposes - SF. Luthfie Arguby Purnomo (Journal on English as a Foreign Language, 2017)
This paper, first of three research parts, attempts to describe the challenges English Letters at IAIN (Institut Agama Islam Negeri/State Islamic Institute) Surakarta faced in implementing gamification for technopreneurial purposes in regard to the transformation of a creative writing class into a ludic writing class, a gamification infused writing class. The challenges revealed are story-game script adaptation, integration portion, and monetization. Specific problems occur on each challenge. Story-game script adaptation exposes three problems namely (1) conditional branching system (2) visualization (3) copyrighted material issues (4) and writing mechanics adaptation. Integration portion challenge displays a problem on the insufficient alloted time for gamifying the creative writing class. Monetization challenge indicates three problems namely (1) the inexistence of monetization team, (2) the inexistence of institutional regulation for monetization management by study programs, (3) responses to gaming trends. Responding to these problems, solutions specifically designed based on the nature of the problems are implemented.